Impact of the use of biologics and their discontinuation on the gut microbiota of psoriasis patients - Penas Steinhardt, Alberto (2025)
Fil: Penas Steinhardt, Alberto. Instituto Universitario de Ciencias de la Salud. Fundación Barceló; Argentina.